(untitled) (Journal of Economic Research & Business Administration, 2016)
Among the activities of a company it is needed to effectively use methods to reduce cost risks Risks affect different aspects of the enterprise, the effects are usually is negative. The article suggests a classification of modern techniques of management of risk, which allows more efficient ways of its use, depending on the nature of the environment changes, and management policy. Each of risk mitigation techniques is differentiated by degrees of impact on the level in a particular situation, as well as the necessary costs of their implementation. The efficiency of the chosen method is largely determined by the situation, as well as the type of risk and industry features of the enterprise. In this article we consider the effectiveness of the implementation of risk management and risk mitigation features, develop techniques like: avoidance, transference, mitigation, acceptance, risk minimization